2020
DOI: 10.1038/s41598-020-61195-9
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of macroporous transition metal hydroxide monoliths via a sol-gel process accompanied by phase separation

Abstract: three-dimensional transition metal hydroxide monoliths were facilely fabricated by a sol-gel process accompanied by phase separation in the presence of polyacrylic acid (pAA) and propylene oxide (po). in the typical Zncl 2 -pAA-po system, pAA is used as a phase separation inducer as well as a framework former to control the phase separation and the formation of macrostructures, whereas po works as a proton scavenger to initiate the gelation of the system and freeze the macrostructures. Appropriate amount of pA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…10). The FE-SEM images revealed that the morphology in all the cases is changed upon conversion from a gel to a xerogel 53,54 (Fig. S29-S32, ESI †).…”
Section: Self-assembly Of Organogels Of G8mentioning
confidence: 99%
“…10). The FE-SEM images revealed that the morphology in all the cases is changed upon conversion from a gel to a xerogel 53,54 (Fig. S29-S32, ESI †).…”
Section: Self-assembly Of Organogels Of G8mentioning
confidence: 99%
“…Transition metal hydroxide porous monoliths have also been developed recently (Table 4), in the presence of PO and HPAA [96], involving low-valence elements (Mn 2+ , Fe 2+ , Co 2+ , Ni 2+ , and Zn 2+ ). Inorganic metal-salts were employed in this case, which undergo hydrolysis to form hydrated metal ions complexes with water molecules.…”
Section: Other Non-siliceous Macroporous Monolithic Systemsmentioning
confidence: 99%
“…Figure 17 displays the pore morphology obtained for varied transition metal hydroxide monoliths synthesized by the epoxide method. The effect of varied synthesis parameters was studied in this work [96]. Larger amounts of water promote the hydrolysis reaction of the Zn precursor and, therefore, an increased number of OH groups at the surface of the oligomers, establishing strong H bonds with HPAA, delaying phase separation, and resulting in finer phase-separated domains.…”
Section: Other Non-siliceous Macroporous Monolithic Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sol–gel process accompanied by phase separation was first reported in the silica system in 1991, and various kinds of metal hydroxide and oxide monoliths have been reported . Some researchers reported nickel hydroxide/poly­(acrylic acid) composite monoliths via the phase separation route. However, a large amount of the organic polymer, poly­(acrylic acid), in the skeletons is difficult to be removed without collapsing the macroporous structures and monolithic forms . Until now, the phase separation approach toward macroporous low-valence metal hydroxide monoliths has not been successfully prepared without the contamination of a large amount of the organic polymer in the metal hydroxide skeletons. Therefore, a synthetic strategy which enables to avoid the contamination of the organic polymer in the skeletons is needed to obtain the pure metallic nickel monolithic electrodes with controlled multiscale porous structures.…”
Section: Introductionmentioning
confidence: 99%